Neoadjuvant chemotherapy in high-risk ovarian cancer patients: Role of age. Issue 2 (April 2019) - Cioffi, Raffaella; Bergamini, Alice; Rabaiotti, Emanuela; Petrone, Micaela; Pella, Francesca; Ferrari, Davide; Mangili, Giorgia; Candiani, Massimo
Objective: To review a single-center clinical experience with neoadjuvant chemotherapy (NACT) in a population of frail epithelial ovarian cancer (EOC) patients and investigate the prognostic role of advanced age. Methods: We retrospectively reviewed clinical data from 102 advanced EOC patients treated with NACT and presenting high perioperative risk. Patients were divided into 2 groups: group A, including patients aged 70 years or older; and group B, including patients below 70 years old. Univariate and multivariate analyses were performed to compare survival and prognostic factors for survival between the two groups. Results: Forty-two patients (41.2%) were older than 70 years. Elderly patients were more likely to present comorbidities ( p = 0.0001), poor performance status ( p = 0.04), and multiple indications for NACT ( p = 0.03). They showed a reduced response to NACT, since only 64% of elderly patients underwent surgical debulking (98.3% vs 64.3%, p = 0.001) and, among these, half of them were optimally debulked (79.3% vs 50%, p = 0.01). Median progression-free survival (PFS) and overall survival (OS) were significantly lower in group A (respectively, 9 vs 13 months, p = 0.005, and 21 vs 29 months, p = 0.01). Advanced age, IV stage, presence of ascites, and residual disease >1 cm were significantly associated with a lower PFS. However, when analyzing factors associated with OS, the only significant ones were higher American Society of Anesthesiologists score and residual disease >1 cm. Conclusions: Age was not found to be a prognostic factor for survival. This highlights the necessity of validated geriatric assessment tools predicting functional age and treatment tolerability to avoid undertreatment of elderly patients.